High importance of autochthonous basal food source for the food web of a Brazilian tropical stream regardless of shading - Neres-Lima, Vinicius; Brito, Ernesto F.; Krsulović, Felipe A. M.; Detweiler, Angela M.; Hershey, Anne E.; Moulton, Timothy P. (International review of hydrobiology., 2016)
According to the prevalent paradigm, the major source of carbon and energy for food webs of small forested streams in temperate regions is allochthonous material from the surrounding forest. Tropical streams have not been as well studied and there has been some speculation that their food webs are more aligned with in‐stream, algal production (autochthonous carbon). We studied food sources and consumers in four sites in a coastal tropical stream with gradients of 36–254 m elevation, 8–73% canopy cover and 11.9–7.1 km2 watershed area, with the expectation that the food web would incorporate proportionately more allochthonous material as shading increased with smaller stream size. We analysed stable isotope ratios of carbon and nitrogen in basal resources and fauna and compared the values of consumers to the potential sources using a mixing model to estimate the proportion of allochthonous and autochthonous material in their diets. The predominant source of carbon in the food web was from algal production at all sites. There was no distinct increase in the proportion of allochthonous contribution to the diets of primary consumers and predators with increasing shading, and they did not generally change their diet with shading. Thus the food web was based more on autochthonous resources than would be expected from the paradigm for temperate streams.